2015
DOI: 10.1039/c4dt01542h
|View full text |Cite
|
Sign up to set email alerts
|

A study on the inhibition of dihydrofolate reductase (DHFR) from Escherichia coli by gold(i) phosphane compounds. X-ray crystal structures of (4,5-dichloro-1H-imidazolate-1-yl)-triphenylphosphane-gold(i) and (4,5-dicyano-1H-imidazolate-1-yl)-triphenylphosphane-gold(i)

Abstract: An unprecedented study on the inhibitory activities of a class of phosphane gold(i) complexes on E. coli dihydrofolate reductase (DHFR) is reported. The gold(i) complexes considered in this work consist of azolate or chloride ligands and phosphane as co-ligands. The ligands have been functionalized with polar groups (-COOH, -COO(-), NO2, Cl, CN) to obtain better solubility in polar media. Neutral, anionic and cationic gold(i) complexes have been tested as DHFR inhibitors by means of a continuous direct spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Folic acid (FA) is a water-soluble vitamin important for biological systems. It is not biologically active per se, but it is the precursor of the active form known as tetrahydrofolate (THF), which is essential for the de novo synthesis of purines, amino acids, and thymidylate (TMP) [13]. It has been demonstrated that its absence causes the inhibition of cell growth and proliferation [14].…”
Section: Physiological Role and Structure Of Dhfrmentioning
confidence: 99%
“…Folic acid (FA) is a water-soluble vitamin important for biological systems. It is not biologically active per se, but it is the precursor of the active form known as tetrahydrofolate (THF), which is essential for the de novo synthesis of purines, amino acids, and thymidylate (TMP) [13]. It has been demonstrated that its absence causes the inhibition of cell growth and proliferation [14].…”
Section: Physiological Role and Structure Of Dhfrmentioning
confidence: 99%
“…Gold compounds C-I and C-II consist of a propeller-shaped hydrophobic PPh 3 moiety and a more polar imidazole head both bonded to the gold(I) atom in a linear geometry. However, as indicated by their experimental partition coefficients log P (+0.87 for C-I and +0.97 for C-II), they are slightly hydrophobic molecules [ 24 ], hence preferring to be located in the hydrophobic region of the host matrix bilayers. This insertion causes an increase in the volume of the hydrophobic moiety and induces the transition towards a more negatively curved mesophase, as observed with loaded GMO and PHYT systems.…”
Section: Resultsmentioning
confidence: 99%
“…Glyceryl monooleate (GMO) was purchased from Merck (Milan, Italy), phytantriol (PHYT) was purchased from TCI Europe and 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) from Avanti Polar Lipids. (4,5-dicloro-1H-imidazolate-1-yl)-(triphenylphosphane)-gold(I) (C-I) and (4,5-dicyano-1H-imidazolate-1-yl)-(triphenylphosphane)-gold(I) (C-II) were synthesized [ 24 ] as previously described; 4,5-dichloro-imidazole and the 4,5-dicyano-imidazole were N–H deprotonated with KOH in THF or with solid K 2 CO 3 in H 2 O/CH 3 OH solution, respectively, and reacted with PPh 3 AuBF 4 in THF solution in a 1:1 mole ratio. The crude reaction mixtures were washed with water and the organic phases taken to dryness.…”
Section: Methodsmentioning
confidence: 99%
“…They were found to possess mechanisms of action that were strongly dependent on their structure. In this regard, some years ago, our group was involved in a pioneer study where, surprisingly, these phosphane gold(I) compounds [13,14] and their relative bis-phosphane gold(I) compounds were found to inhibit DHFR from E. coli in the micromolar range of concentration [15]. This latter work was done with the double goal to contribute to the shared hypothesis that bioactive anticancer or antimicrobial gold(I) phosphane compounds interact with different enzymes, depending on (even mild) structural modifications [16,17], and with the aim to find new inhibitors of DHFR.…”
Section: Introductionmentioning
confidence: 99%